2015
DOI: 10.1111/2047-3095.12122
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nursing Care Based on Comfort Theory on Women's Postpartum Comfort Levels After Caesarean Sections

Abstract: It is recommended that nursing care outcomes be compared using different nursing models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…In the simulation situation, students play a certain role in it, actively participate in practical activities, think and explain according to learning theory, and give students more opportunities to express and think [ 1 ]. Actively participating in classroom learning activities is conducive to improving the enthusiasm of classroom teaching, improving the openness of teaching, and enabling students to better grasp the knowledge of obstetrics and gynecology nursing [ 2 ].…”
Section: Related Workmentioning
confidence: 99%
“…In the simulation situation, students play a certain role in it, actively participate in practical activities, think and explain according to learning theory, and give students more opportunities to express and think [ 1 ]. Actively participating in classroom learning activities is conducive to improving the enthusiasm of classroom teaching, improving the openness of teaching, and enabling students to better grasp the knowledge of obstetrics and gynecology nursing [ 2 ].…”
Section: Related Workmentioning
confidence: 99%
“…According to the Comfort Theory, nurses provide comfort and take precautions related to comfort, and they provide care and assistance by encouraging individuals/families/society and supporting coping methods (Kolcaba, 2003). This theory was proven to positively affect health outcomes in different groups (Aksoy Derya & Pasinlioğlu, 2017; Bice et al, 2018; Bortolusso et al, 2007; Kolcaba & DiMarco, 2005; Kolcaba & Wilson, 2002; Krinsky et al, 2014; Novak et al, 2001; Wilson & Kolcaba, 2004). To the best of our knowledge, this study is the first randomised controlled study to test the effect of a nursing care programme based on the Comfort Theory for paediatric day surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the number of studies on comfort during the postpartum period is very limited 23–26. In her master's thesis, Karakaplan23 reported that 58% of mothers who had normal vaginal delivery stated that they received good care and 52% of them stated that the care they received in their postpartum period did not affect their comfort.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the number of studies on comfort during the postpartum period is very limited. [23][24][25][26] In her master's thesis, Karakaplan 23 reported that 58% of mothers who had normal vaginal delivery stated that they received good care and 52% of them stated that the care they received in their postpartum period did not affect their comfort. This suggests that mothers find routine practices insufficient and that there is a need for additional practices to improve comfort and add value to routine practices.…”
Section: Effect Of Foot Massage On Postpartum Comfort and Painmentioning
confidence: 99%